Braille-iant Cookies / Azrina Fuad - Fuad, Azrina (2020)
Braille-iant Cookies is the latest product from I See You. Inc which is Braille cookie packaging that makes everyone feel what type of cookie it is. The main reason of our company to produce Braille-iant Cookies is to help the visually impaired community and elderly who have vision loss around the world especially in Malaysia. Our company is the first company to introduce Braille writing on food package in Malaysia. We can see that certain people especially independent visually impaired communities are having trouble obtaining important information on products that they want to purchase. So, our focus is to ease the burden of this group of people and make shopping easier for them. Overall marketing strategy includes specific marketing philosophy and strategy of the company, the value chain and channel of distribution in the target market. Our target market will be focused on hypermarkets all over Malaysia especially major hypermarkets in the urban area where the population density is high. The first step in our marketing strategy is determining the target group. We assume that visually impaired people and elderly would be the perfect target customers as this product can make their lives easier as they can only read Braille to obtain any information. Besides that, this product is very easy to use and access. The price offered is also very affordable and reasonable for people from all background. The target production of our company for second year is RM 70 000. The management team of our company is divided into several sections and each of the section were led by experienced and professional employee to ensure our company’s product quality and efficiency.